2017
DOI: 10.2337/dc17-0697
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Diabetes on Long-term Survival Outcomes in Patients With Heart Failure: A Meta-analysis

Abstract: This updated meta-analysis shows that the presence of diabetes per se adversely affects long-term survival and risk of hospitalization in patients with acute and chronic HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 77 publications
5
54
0
8
Order By: Relevance
“…A recent meta‐analysis of 31 registries and 12 clinical trials with 381 725 patients with acute and chronic HF, with a median follow‐up of 3 years confirms that T2DM is independently associated with a higher risk of all‐cause death (random‐effects HR 1.28), CV death (HR 1.34), hospitalization (HR 1.35), and the combined endpoint of all‐cause death or hospitalization (HR 1.41), and the observed long‐term risk appears greater in patients with chronic than in those with acute HF …”
Section: Type 2 Diabetes Mellitus Clinical Status and Outcomes In Pamentioning
confidence: 98%
“…A recent meta‐analysis of 31 registries and 12 clinical trials with 381 725 patients with acute and chronic HF, with a median follow‐up of 3 years confirms that T2DM is independently associated with a higher risk of all‐cause death (random‐effects HR 1.28), CV death (HR 1.34), hospitalization (HR 1.35), and the combined endpoint of all‐cause death or hospitalization (HR 1.41), and the observed long‐term risk appears greater in patients with chronic than in those with acute HF …”
Section: Type 2 Diabetes Mellitus Clinical Status and Outcomes In Pamentioning
confidence: 98%
“…A recent metaanalysis, including 31 registries and 12 clinical trials (combining studies of both acute and chronic heart failure), concluded that diabetes mellitus is independently associated with a higher risk of all-cause death (HR 1.28; 95% CI, 1.21-1.35). 73 Diabetes likely has deleterious effects in all forms of heart failure, including HFrEF and HFpEF, and both ischemic and nonischemic cardiomyopathy. Therefore, it is important to identify and treat risk factors for diabetes early to avoid the morbidity and mortality associated with diabetes and associated conditions, especially heart failure.…”
Section: S8mentioning
confidence: 99%
“…Such uncertainty has led to the proliferation of new risk scores appearing in the literature in the last years, with mixed results [41][42][43][44][45][46][47]. As a partial solution to improve models' effectiveness, recent published studies included cohorts restricted to specific classes of patients (for example, elderly or diabetic) [48,49]. These attempts have led to tailored models and risk scores [50,51] with better but still not optimal performance.…”
Section: Introductionmentioning
confidence: 99%